The effect of evaporative cooling on pistachio bloom delay - Uzun M.; Caglar S. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The aim of this research was to delay pistachio blooming by evaporative cooling including water sprinkling to cool fruit buds. Water was supplied to trees of Uzun, Siirt and Ohadi cultivars starting when 600 chill units were accumulated for rest completion. The effects of evaporative cooling on bud swell, first bloom, full bloom and bloom termination of pistachio cultivars were determined. In all of the three cultivars, differences between watered and unwatered treatments were apparent. The minimal delay was achieved in bud swell (5 days), but it was more effective in delaying the further blooming stages. First bloom of trees (7 days in Uzun, 9 days in Ohadi and 11.5 days in Siirt cultivar). Similarly, full bloom was delayed for 7 days in Uzun, 8.5 days in Ohadi and 12.5 days in Siirt. Bloom termination was delayed for 4.5 days in Uzun, 8.5 days in Ohadi and 9.5 days in Siirt cultivar.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)